Simultaneous Roadside and Urban Background Measurements of Submicron Aerosol Number Concentration and Size Distribution (in the Range 20–800 nm), along with Chemical Composition in Strasbourg, France - Mélodie Chatain; Raphaël Alvarez; Aurélien Ustache; Emmanuel Rivière; Olivier Favez; Cyril Pallares (Atmosphere, 2021)
The adverse health impact of particles and ultrafine particles (UFP) is proven, highlighting the need of measuring the particle number concentration (PNC) dominated by UFP. So far, PNC had never been measured in the Strasbourg urban area (France). The present study on particle size distribution and PNC measurements by an UFP-3031 analyzer was conducted during winter 2019 on a background and a roadside multi-instrumented sites (Black Carbon, chemical speciation, particulate matter 10 μm or less in diameter—PM10 mass). This paper shows significantly higher particle number concentrations of particles below 100 nm at the traffic site compared to the background site. The presence of a road axis thus mainly influences UFP, contrary to larger particles whose levels are more homogeneous over the agglomeration. During the measurement period, the nature of the particles (particle size contribution and chemical composition) was different between periods of high PM10 mass concentrations and periods of high PNC. High PM10 mass concentrations were associated with a high contribution of particles larger than 100 nm but they did not show specific chemical signature. On the other hand, during the periods with high PNC, the chemical composition was modified with an increase of the primary carbonaceous fraction compared to the periods with low PNC, but there was then no clear change in size distribution. Overall, this study illustrates that PM10 mass concentrations were barely representative of UFP and PNC variations, confirming that the monitoring of the latter metrics is necessary to better evaluate the particles toxicity, knowing that this toxicity also depends on the particle’s chemical composition.